HUMAN SECURITY IN EAST AFRICA: THE EAC'S ILLUSIVE QUEST FOR INCLUSIVE CITIZENSHIP (The Strategic Review for Southern Africa, 2020)
The East African Community (EAC) exemplifies the contradiction of independent Africa's efforts to champion regional integration and the idea of pan-Africanism, whilst maintaining the nation-state model left from colonialism. EAC I, 1967-1977, ultimately collapsed due to its inability to create a regional institutional framework that could supplant the nationalist tendencies of its member states' leaders; and failing to adopt a people-centred inclusive approach to its structure and actions. The resultant human security issues suffered throughout post-colonial East Africa at their essence have been caused by the victorious nationstate's continued failure to offer this inclusive citizenship to its peoples. Despite the EAC II's, 2001-present, espoused people-centred reincarnation, it too has so far failed to create the inclusive citizen, or peoplecentred approach to its development and so risks the continued insecurity of its people.